2019
DOI: 10.1177/2325967119s00383
|View full text |Cite
|
Sign up to set email alerts
|

Healing Rates of Massive Rotator Cuff Tears by Allograft Reconstruction vs Maximal Repair - A Prospective Randomized Controlled Trial

Abstract: Objectives: To determine the healing rate of rotator cuff reconstruction with an acellular human dermal allograft compared with the current gold standard arthroscopic maximal rotator cuff repair of large, chronic tears of the rotator cuff. Methods: Thirty patients with a two-tendon chronic retracted rotator cuff tear were enrolled in the study and were randomly allocated (15) to each group. All the patients were evaluated for structural integrity of repair using a 1.5 T MRI at an average of 15 months after sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…11 In 2015, Johns and Snyder 13 also reported bridging the gap using acellular human dermal allograft as a viable solution for massive irreparable rotator cuff tears. We recently completed a prospective randomized controlled trial comparing bridging reconstruction with maximal repair 14 and found that the re-tear rate in the bridging reconstruction group was significantly lower than for the repair group at the 1-year postoperative timepoint. Furthermore, we did note that progression of cuff arthropathy was more prevalent in the repair group as compared to the reconstruction group.…”
mentioning
confidence: 99%
“…11 In 2015, Johns and Snyder 13 also reported bridging the gap using acellular human dermal allograft as a viable solution for massive irreparable rotator cuff tears. We recently completed a prospective randomized controlled trial comparing bridging reconstruction with maximal repair 14 and found that the re-tear rate in the bridging reconstruction group was significantly lower than for the repair group at the 1-year postoperative timepoint. Furthermore, we did note that progression of cuff arthropathy was more prevalent in the repair group as compared to the reconstruction group.…”
mentioning
confidence: 99%